Risk of electrocoagulation syndrome after endoscopic submucosal dissection in the colon and rectum - Jung, Dahyun; Youn, Young Hoon; Jahng, Jaehoon; Kim, Jie-Hyun; Park, Hyojin (Endoscopy, 2013)
Background and study aims: The risk of post endoscopic submucosal dissection electrocoagulation syndrome (PEECS) is unknown. We aimed to investigate the incidence and clinicopathologic risk factors associated with PEECS after colorectal endoscopic submucosal dissection (ESD). Patients and methods: All patients treated with colorectal ESD between 2009 and 2011 by a single expert ESD endoscopist at Gangnam Severance Hospital, Seoul, Korea were included in this retrospective study. Patients who had fever, regional rebound tenderness, or marked leukocytosis after ESD were defined as having PEECS. Results: 89 patients were treated during the study period. Six patients with microperforation and one patient with overt perforation were excluded. Thus, 82 cases without perforation were analyzed. The risk of PEECS was 40.2 %. In the PEECS group, the mean size of resected specimens was larger and mean procedure time was longer than in the patients without PEECS. The risk of PEECS was significantly lower for patients with carcinoid tumors, and for ESD in the rectosigmoid area. Piecemeal resection was significantly associated with the development of PEECS. In multivariate analysis, lesion size larger than 3 cm (odds ratio [OR] 5.0, 95 % confidence interval [95 %CI] 1.2 – 21.7) and site other than rectosigmoid (OR 7.6, 95 %CI 2.1 – 27.9) were independent risk factors for PEECS. Conclusions: Large tumor size and tumor site other than rectosigmoid were independent risk factors related to PEECS. Patients with tumors larger than 3 cm, in colon areas other than the rectosigmoid, should be observed carefully after colorectal ESD.